Effectiveness of nine control methods of Oregmopyga peruviana (Granara de Willink & Diaz) (Hemiptera: Coccoidea: Eriococcidae) in Vitis vinifera L. ‘Negra Criolla’ and ‘Quebranta’ - Dadther-Huaman, Hans (2020)
Oregmopyga peruviana, pest of the vine, causes damage that reduce the yield and strong infestations provoke the death of the plant. It is present along the Peruvian coast, being a very important pest. The objective of the study is to determine the individual efficacy of nine treatments (buprofezin 25 g·hL-1, chlorpyrifos 96 g·hL-1, pure vinasse, spirotetramat 474.3 g·hL-1, imidacloprid SC 1435 g·hL-1, imidacloprid WG 17.5 g·hL-1, M. anisopliae and B. bassiana 333.3 x 1012 CFU·hL-1, thiamethoxam 900 g·hL-1 and dinotefuran 680 g·hL-1) in different phenological periods. Each treatment was compared with its control using the Student's t-test for independent variables (p ≤ 0.05). In addition, the control percentage was determined using the Henderson and Tilton formula, obtaining for buprofezin 87.4%, chlorpyrifos 84.2%, vinasse 70.1%, spirotetramat 97.2%, imidacloprid WG 95.5%, imidacloprid SC 87.6%, dinotefuran 99.6% and thiamethoxam 91.6%. M. anisopliae and B. bassiana got no control. The results show that eight of the nine treatments had a controlling percentage higher than 70% having significantly lower populations. Furthermore, vinasse is an organic and low cost alternative for the control of O. peruviana.